2008
DOI: 10.1097/crd.0b013e31815aff8b
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Rehabilitation Barriers and Opportunities Among Women With Cardiovascular Disease

Abstract: Cardiac rehabilitation is a key component of the comprehensive care of the 79.4 million adults in the United States with one or more forms of cardiovascular disease. Only a fraction of eligible candidates complete cardiac rehabilitation and women are at a significantly higher risk for underutilizing this safe and effective secondary prevention intervention. This article reviews the complex array of barriers to cardiac rehabilitation, with a focus on those factors that are unique to women. The Healthcare Utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 98 publications
(305 reference statements)
1
30
0
Order By: Relevance
“…Patient-level factors affecting CR enrollment incorporated into the surveys were those shown in the literature to be related to CR [20,21] and are again in accordance with Andersen's Model [19] (Figure 1). Andersen conceptualizes the patient-level factors as: (1) characteristics predisposing utilization, (2) characteristics enabling utilization, and (3) need.…”
Section: Methodsmentioning
confidence: 72%
“…Patient-level factors affecting CR enrollment incorporated into the surveys were those shown in the literature to be related to CR [20,21] and are again in accordance with Andersen's Model [19] (Figure 1). Andersen conceptualizes the patient-level factors as: (1) characteristics predisposing utilization, (2) characteristics enabling utilization, and (3) need.…”
Section: Methodsmentioning
confidence: 72%
“…18 The majority of information available about the cardiovascular benefits has been derived from studies predominantly in men, despite the fact that the rehabilitation process seems to play an ascertainable role in improving quality of life, exercise tolerance, and optimization of risk factors in women as well [19][20][21] when specific needs of women during CR are considered. [22][23][24] Nevertheless, women are less likely to be enrolled in CR programs, especially after cardiac surgery. 25,26 Furthermore, the continuous participation and completion rates of formal cardiac rehabilitation programs remain inferior compared with men.…”
Section: Discussionmentioning
confidence: 98%
“…Parkosewich 3 recently reviewed the relevant literature on this topic and reported that the proportion of referred patients enrolling in CR ranges from 11% to 69% (citing 11 studies), and dropout rates range from 12% to 47% (citing 6 studies). The evidence on the role of gender in predicting CR completion is conflicting, 3 with some studies reporting that female gender is a significant negative predictor 4,5 and other studies finding no significant difference between men and women completing CR. 6 Studies that are from the early to mid-1990s reported that women who are white are more likely to complete the prescribed number of sessions compared with black women, 7 and younger women and those who smoke are less likely to complete a CR program.…”
mentioning
confidence: 92%
“…Referral alone is not sufficient to achieve high rates of enrollment, 3 and the lack of effective strategies to overcome barriers women face to enrollment is a major problem in this field of research and in practice. Studies have shown that enrollment rates among referred patients range from 33% to 80%; 10,11 the likelihood of enrollment is lower among patients who are female, older, or an ethnic minority.…”
mentioning
confidence: 99%